ANALYZING FACTORS THAT AFFECTING PRODUCT LIFE CYCLE OF BEVERAGE PRODUCT BROWNICE BEVERAGE AND PASTRY - Sineleyan, Verren Jilly; Massie, James D. D.; Wangke, Shinta J. C. (Universitas Sam Ratulangi, 2019)
Abstract: Drinking is a basic human needs that cannot be denied. In fact, to release your thirst there are alternative drinks that have a variety of flavors to meet our needs for our body. From there the current development and the interest of business people to make the beverage business increase and compete to produce innovations that attract the attention of customers. The purpose of this study is to determine the factors that affecting the product life cycle of Brownice beverage products. This study uses quantitative method using a questionnaire to obtain data and use purposive sampling as a sampling technique where 100 customers from Brownice Beverage and Pastry as respondents. This study uses factor analysis as an analysis tool. The results of this study indicates that factors there are 5 factors formed that affecting the product life cycle, namely: Customer Perception, Advertising, Promotion, Customer Perceive Value and Service Quality. Based on the results of the study, recommendations for Brownice Beverage and Pastry owners and entrepreneurs who want to open a beverage business should pay attention to these factors to create indicators or strategies when to launch a product forward.Keywords: beverage product, product life cycle, factor analysis